Human rights: between universalism and relativism - Van Engeland, Anicée (Springer, 2022)
The connection between human rights, peace and security highlights the stakes attached to the respect and enforcement of the principle of universality. Yet the 1948 Universal Declaration of Human Rights and all subsequent international conventions have been questioned by States and communities: they are believed to be reflective of euro-centric values. This is why cultural relativism has emerged as an alternative to the principle of universality of human rights. This raises security questions: if a state questions universality of human rights, does it undermine the whole UN peace and security system? Is cultural relativism a threat to universality, leading to fragmentation and insecurity? The book chapter seeks to address such issues while looking at transcending the dichotomy between universalism and relativism. Scholars’ views and strategies to overcome the tensions and ensure the respect of human rights while promoting peace and security are consequently examined.
Keywords: Human Rights; Universality; Cultural Relativism